Peran Penyiar Dalam Melaksanakan Teknik Siaran Program UNPOOP OZ Radio Jakarta Dalam Menarik Minat Pendengarnya - Muhammad Edward Dewantoro; R. Hiru Muhammad (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
OZ Radio Jakarta has a weekly program called UNPOP (Unpopular Opinion). The presence of the UNPOP program in the last few months has been able to attract the attention of the public as well as making OZ Radio Jakarta in the top 3 favorite radio stations in Jakarta after Prambors and Mustang FM. Because in this program the broadcaster has a unique way of conveying information. The broadcaster presented his program in a more relaxed manner, seemed familiar, but was able to control his listeners. Therefore, this research aims to determine the role of broadcasters in implementing broadcast techniques and determine the inhibiting and supporting factors for broadcasters in implementing broadcast techniques on the UNPOP OZ Radio Jakarta program in attracting the interest of listeners. In this research, researchers used Broadcaster Role Theory and Broadcast Engineering Theory. This research includes qualitative research with descriptive methods. Data collection techniques carried out by researchers were through in-depth interviews, documentation and direct observation at OZ Radio Jakarta. The results of this research show that the roles used by the broadcasters of the UNPOP OZ Radio Jakarta program include five aspects, namely the role of involving listeners (interactive), the role of speaking rather than speaking, the role of maximizing body expression, the role of a radio showcase and the role of a good listener. This research also found that the selection of broadcast techniques in the UNPOP OZ Radio Jakarta program predominantly uses Ad Libitum broadcast techniques, however there are several situations that require broadcasters to use script reading broadcast techniques such as doing Ad Libs or important information that cannot be improvised.